The Vedic concept of work ethic and its relevance to 21st century competencies - Untara, I Made Gami Sandi; Sumaryani , Ni Made; Surpi, Ni Kadek (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Introduction: The Vedas and Hindu Susastra teach humanity to live in a superior way through a good work ethic. Work ethic is a very important basic value instilled in the Vedas. Work ethic will lead humanity to prosperity. Work ethic is a basic skill in the Vedas that can be developed according to the needs of the times. Method: This article is the result of text research, which examines the content and meaning of the text, as well as its structure and discourse. The data was obtained through a literature study. The qualitative data in the form of texts have been examined through philological work, although it is not as rigorous as philological studies in general. Finding: This article is the result of text research and finds its context or spirit in the 21st century which has different characteristics from previous centuries. The 21st century, characterised by the development of science and technology, has changed many things in human life, including the type and way of working. However, the work ethic taught in the Vedas such as being diligent, persistent, creative, strong and good at managing finances is the basic capital in life. Conclusion: In the 21st century, the need for skills such as communication, creativity and innovation, collaboration and critical thinking actually find a link to the spirit and values taught in the past. Hindus strongly emphasise logic and critical thinking skills as the spirit of the 21st century. Therefore, the Vedic spirit should find a good place and encourage humans to live more excellently in this century